2015
DOI: 10.1099/ijs.0.068916-0
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium sophorae sp. nov. and Rhizobium sophoriradicis sp. nov., nitrogen-fixing rhizobial symbionts of the medicinal legume Sophora flavescens

Abstract: Five bacterial strains representing 45 isolates originated from root nodules of the medicinal legume Sophora flavescens were defined as two novel groups in the genus Rhizobium based on their phylogenetic relationships estimated from 16S rRNA genes and the housekeeping genes recA, glnII and atpD. These groups were distantly related to Rhizobium leguminosarum USDA 2370 T (95.6 % similarity for group I) and Rhizobium phaseoli ATCC 14482 T (93.4 % similarity for group II) in multilocus sequence analysis. In DNA-DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(20 citation statements)
references
References 25 publications
1
18
0
1
Order By: Relevance
“…The ML tree of the 16S rRNA gene sequences (1318 nt) showed that the four isolates had identical 16S rRNA genes, which had the same sequence as those of R. leguminosarum USDA 2370 T , R. laguerreae FB206 T , Rhizobium indigoferae CCBAU 71042 T and Rhizobium sophorae CCBAU 03386 T , a novel species described recently (Jiao et al, 2015) (, Table S2). The similarities between the isolates and type strains of species of the genus Rhizobium varied from 95.6 to 100 %.…”
mentioning
confidence: 77%
“…The ML tree of the 16S rRNA gene sequences (1318 nt) showed that the four isolates had identical 16S rRNA genes, which had the same sequence as those of R. leguminosarum USDA 2370 T , R. laguerreae FB206 T , Rhizobium indigoferae CCBAU 71042 T and Rhizobium sophorae CCBAU 03386 T , a novel species described recently (Jiao et al, 2015) (, Table S2). The similarities between the isolates and type strains of species of the genus Rhizobium varied from 95.6 to 100 %.…”
mentioning
confidence: 77%
“…The analysis of the recA and atpD housekeeping genes allows the differentiation of rhizobia at the species level and they are available for most described species able to nodulate legumes to date [14,40,41]. The similarity values for the recA and atpD genes among the isolated strains ranged from 98.7% to 97.1% and 98.8% to 90.1%, respectively.…”
Section: Phylogenetic Analysis Of Housekeeping Genesmentioning
confidence: 99%
“…Cell motility was assayed by development of turbidity in test tube containing semisolid TSA medium (0.4 % agar), after 2 days of incubation at 28 °C (Cowan and Steel 1965). Cell dimension and appearance were observed by using a Hitachi S-3400 scanning electron microscope (SEM), and the sample was prepared using the protocol of Jiao et al (2015). Bacterial growth was tested at 28 °C on LB agar, nutrient agar (NA), International Streptomyces Project (ISP) 1 medium (Pridham and Gottlieb 1948), ISP 4 medium (Shirling and Gottlieb 1966), Czapek's agar and ISP 5 medium (Pridham and Lyons 1961).…”
Section: Morphological Physiological and Biochemical Characterizationmentioning
confidence: 99%